LIR motif-containing hyperdisulfide β-ginkgotide is cytoprotective, adaptogenic, and scaffold-ready - Dutta, Bamaprasad (2019)
Grafting a bioactive peptide onto a disulfide-rich scaffold is a promising approach to improve its structure and metabolic stability. The ginkgo plant-derived β-ginkgotide β-gB1 is a highly unusual molecule: Small, hyperdisulfide, and found only in selected ancient plants. It also contains a conserved 16-amino-acid core with three interlocking disulfides, as well as a six-amino-acid inter-cysteine loop 2 suitable for grafting peptide epitopes. However, very little is known about this recently-discovered family of molecules. Here, we report the biophysical and functional characterizations of the β-ginkgotide β-gB1 from G. biloba. A circular dichroism spectroscopy analysis at 90 °C and proteolytic treatments of β-gB1 supported that it is hyperstable. Data mining revealed that the β-gB1 loop 2 contains the canonical LC3 interacting region (LIR) motif crucial for selective autophagy. Cell-based assays and pull-down experiments showed that β-gB1 is an adaptogen, able to maintain cellular homeostasis through induced autophagosomes formation and to protect cells by targeting intracellular proteins from stress-mediated damage against hypoxia and the hypoxia-reoxygenation of induced cell death. This is the first report of an LIR-containing peptide natural product. Together, our results suggest that the plant-derived β-ginkgotide is cytoprotective, capable of targeting intracellular proteins, and holds promise as a hyperdisulfide scaffold for engineering peptidyl therapeutics with enhanced structural and metabolic stability.